Gender differences in lower extremity coupling variability during an unanticipated cutting maneuver - Pollard, C. D.; Heiderscheit, B. C.; van Emmerik, R. E. A.; Hamill, J. (Journal of Applied Biomechanics, 2005)
The purpose of this study was to determine if gender differences exist in the variability of various lower extremity (LE) segment and joint couplings during an unanticipated cutting maneuver. 3-D kinematics were collected on 24 college soccer players (12 M, 12 F) while each performed the cutting maneuver. The following intralimb couplings were studied: thigh rotation (rot)/leg rot; thigh abduction-adduction/leg abd-add; hip abd-add/knee rot; hip rot/knee abd-add; knee flexion-extension/knee rot; knee flx-ext/hip rot. A vector-coding technique applied to angle-angle plots was used to quantify the coordination of each coupling. The average between-trial standard deviation of the coordination pattern during the initial 40% of stance was used to indicate the coordination variability. One-tailed t-tests were used to determine differences between genders in coordination variability for each coupling. Women had decreased variability in four couplings: 32% less thigh rot/leg rot variability; 40% less thigh abd-add/leg abd-add variability; 46% less knee flx-ext/knee rot variability; and 44% less knee flx-ext/hip rot variability. These gender differences in LE coordination variability may be associated with the increased incidence of ACL injury in women. If women exhibit less flexible coordination patterns during competition, they may be less able to adapt to the environmental perturbations experienced during sports. These perturbations applied to a less flexible system may result in ligament injury.